The effect of sandblasting on surface properties for adhesion. (October 2016) - Rudawska, Anna; Danczak, Izabela; Müller, Miroslav; Valasek, Petr
Abstract: The paper presents the effect of sandblasting on surface properties of steel for adhesion. The investigated parameters included pressure (1, 2 and 4 bars) and four types of abrasive material, each material type being of different granulation. In the experiments the effect of the above variables on the surface roughness, contact angle Θ, work of adhesion Wa and surface free energy γ was investigated. It has been shown in this research that surface properties are more affected by abrasive material type applied rather than by the sandblasting process parameters.